The effectiveness of oral health education and toothbrush training in decreasing plaque index score among Elementary Students in Jakarta - Helwiah Umniyati; Benanziski Miegasivia; Muhamad Zakki (Journal of Dentomaxillofacial Science, 2020)
Objective: to know the effectiveness of dental health education on decreasing plaque index score and increasing salivary pH among elementary school children in SD 01 Pagi Kampung Rawa, Central Jakarta. Material and Methods: quasi experimental study with pre and post-test design among 93 students which divided into four groups, group 1: control group, group 2: education group without tooth brushing training, group 3: education with 1 times tooth brushing training and group 4: education + 4 times tooth brushing training. The plaque index assessed by the Personal Hygiene Performance Index (PHP) method. Data analysis performed with Kruskall Wallis, Mann-Whitney, and Wilcoxon using SPSS 23. Results: At baseline there were no significant difference on plaque score among four groups (p>0.05). There was significant decreasing in plaque score after intervention in group 2, 3 and 4 (p< 0.005), but not in group control. When analyzing plaque score after intervention among four groups, there was no significant difference on plaque score between group 1 (control) and group 2. There was significant difference on plaque score between group 1 and group 3 or 4. There were significant difference on plaque score between group 2 and group 3 or 4. There was no significant difference on plaque score between group 3 and group 4. Conclusion: Dental health education with tooth brushing training is an effective way to reduce the plaque index score.